Clima laboral y rotación de personal en la agencia agraria de Ucayali Contamana 2024 - Diaz Gonzalez, Victor Kenny Andrey (2025)
The present research aimed to determine the relationship between work environment and staff turnover at the Agrarian Agency of Ucayali, Contamana 2024. A descriptive and correlational study was carried out, with a quantitative approach and a non-experimental cross-sectional design, which allowed the variables to be analyzed without manipulating them, obtaining data at a single point in time. To measure the relationship between both variables, the Pearson correlation coefficient was used, which resulted in 0.845, indicating a strong positive correlation. Furthermore, the bilateral significance level obtained was 0.000, confirming that the relationship is statistically significant. These findings support the alternative hypothesis (Ha), which suggests that a better work environment contributes to reducing staff turnover, while an unfavorable environment increases job instability. The importance of this study lies in its contribution to organizational management, as it demonstrates the need to strengthen internal communication, improve working conditions, and promote motivational strategies to reduce turnover. In conclusion, it is confirmed that there is a significant relationship between the work environment and staff turnover, highlighting the importance of creating a favorable work environment to ensure the permanence and stability of human talent at the Ucayali Agrarian Agency, Contamana 2024.